2005
DOI: 10.1038/sj.cdd.4401826
|View full text |Cite
|
Sign up to set email alerts
|

Targeting XIAP for the treatment of malignancy

Abstract: X-linked inhibitor of apoptosis protein (XIAP) is a member of the inhibitor of apoptosis proteins family of caspase inhibitors that selectively binds and inhibits caspases-3, -7 and -9, but not caspase-8. As such, XIAP blocks a substantial portion of the apoptosis pathway and is an attractive target for novel therapeutic agents for the treatment of malignancy. Antisense oligonucleotides directed against XIAP are effective in vitro and are currently being evaluated in clinical trials. Small molecule XIAP inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
246
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(252 citation statements)
references
References 72 publications
3
246
0
3
Order By: Relevance
“…However, elevated levels of IAPs are often associated with resistance to apoptosis in human cancer cells and lowering IAPs using SMAC mimetics is known to sensitise cells to cytotoxic agents. 140,141 Perspectives It has been around 15 years since the first caspase was discovered. During this time, the pendulum has shifted from earlier predictions that all caspases play some role in the execution of apoptosis, to caspases may not be required for many forms cell deaths.…”
Section: Regulators Of Mammalian Caspasesmentioning
confidence: 99%
“…However, elevated levels of IAPs are often associated with resistance to apoptosis in human cancer cells and lowering IAPs using SMAC mimetics is known to sensitise cells to cytotoxic agents. 140,141 Perspectives It has been around 15 years since the first caspase was discovered. During this time, the pendulum has shifted from earlier predictions that all caspases play some role in the execution of apoptosis, to caspases may not be required for many forms cell deaths.…”
Section: Regulators Of Mammalian Caspasesmentioning
confidence: 99%
“…Further, studies have revealed that of the three BIR domains of XIAP, BIR-2 inhibits the downstream caspase-3 and caspase-7, whereas BIR-3 inhibits the upstream caspase-9 (19 -21). In light of its frequent overexpression in human cancers and its known function as a roadblock to apoptosis, XIAP also represents a candidate therapeutic target in cancer cells (22).…”
Section: Introductionmentioning
confidence: 99%
“…The eight known members of the human IAP family are characterized by at least one baculoviral IAP repeat (BIR), a domain known to bind caspases, the proteases responsible for apoptosis. Several IAPs also contain an E2-binding RING finger domain at the carboxy terminus imparting E3 ligase activity, which mediates both autoubiquitination and ubiquitination of various substrates (Salvesen and Duckett, 2002;Eckelman et al, 2006;Schimmer et al, 2006). Cellular IAP1 and IAP2 were first identified by their association with TNFa-receptorassociated factors À1 and À2 (TRAFs), adapter proteins that associate with various members of the tumor necrosis factor (TNF) receptor family and that mediate activation of protein kinases involved in NF-kB induction and other signal transduction events (Rothe et al, 1995).…”
Section: Introductionmentioning
confidence: 99%